2018
DOI: 10.1101/242263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA barcodes and insights into the phylogenetic relationships of butterflies of the genusEurema(Pieridae) from Uttarakhand, India

Abstract: In DNA barcoding, mitochondrial gene cytochrome c oxidase I recommended as a tool for the rapid identification and discovery of species. Genus Eurema, Family Pieridae is a highly diverse and distributed along wide geographic ranges in the world as well as India including approximately 70 species throughout the world. The present study is preliminary approach, we included n=12 specimen (3 samples per species) of four different Eurema species, listed in IUCN as Least concern species, were collected from Uttarakh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These include the identification of disease vectors (Tabanid flies: Banerjee et al, 2015; sand flies: Gajapathy et al, 2016; biting midges Culicoides: Harrup et al, 2016; mosquitos: Weeraratne et al, 2018), and also of highly invasive agricultural pests (fruit fly: Khamis et al, 2012; tea mosquito bugs: Rebijith et al, 2012; Pentatomomorpha bugs: Tembe et al, 2014; Kaur & Sharma, 2016; thrips: Tyagi et al, 2017; and fall armyworm: Nanayakkara et al, 2020). Furthermore, barcoding approaches have been used to resolve taxonomic questions in butterflies (Goonesekera et al, 2019; Rajpoot et al, 2018), fishes (Dhaneesh et al, 2015; Ekanayake et al, 2021; Lakra et al, 2016; Raja & Perumal, 2017; Senevirathna & Munasinghe, 2013), frogs (Biju et al, 2014; Meegaskumbura et al, 2015), freshwater crabs (Beenaerts et al, 2010), spiders (Ileperuma Arachchi & Benjamin, 2019; Kanesharatnam & Benjamin, 2019), snakes (Pyron et al, 2013), and snails (Raheem et al, 2017). Concerted and comprehensive initiatives, which coordinate the sampling and data basing efforts, as known from Europe and northern America, for example, are yet missing.…”
Section: Introductionmentioning
confidence: 99%
“…These include the identification of disease vectors (Tabanid flies: Banerjee et al, 2015; sand flies: Gajapathy et al, 2016; biting midges Culicoides: Harrup et al, 2016; mosquitos: Weeraratne et al, 2018), and also of highly invasive agricultural pests (fruit fly: Khamis et al, 2012; tea mosquito bugs: Rebijith et al, 2012; Pentatomomorpha bugs: Tembe et al, 2014; Kaur & Sharma, 2016; thrips: Tyagi et al, 2017; and fall armyworm: Nanayakkara et al, 2020). Furthermore, barcoding approaches have been used to resolve taxonomic questions in butterflies (Goonesekera et al, 2019; Rajpoot et al, 2018), fishes (Dhaneesh et al, 2015; Ekanayake et al, 2021; Lakra et al, 2016; Raja & Perumal, 2017; Senevirathna & Munasinghe, 2013), frogs (Biju et al, 2014; Meegaskumbura et al, 2015), freshwater crabs (Beenaerts et al, 2010), spiders (Ileperuma Arachchi & Benjamin, 2019; Kanesharatnam & Benjamin, 2019), snakes (Pyron et al, 2013), and snails (Raheem et al, 2017). Concerted and comprehensive initiatives, which coordinate the sampling and data basing efforts, as known from Europe and northern America, for example, are yet missing.…”
Section: Introductionmentioning
confidence: 99%
“…In the numerous studies were reported that only morphological data were unable to give unequivocal answers, but the combined analyses (morphological and molecular analyses) have given a robust phylogenetic estimate for Lepidoptera in recent years (CHEN et al, 2019;MALYSH, 2013;TRANKNER et al, 2009;WAHLBERG et al, 2005). In addition, it is emphasized that morphologically defined species should be supported with molecular analyses for species delimination or phylogenetic position (KEMAL et al, 2019;RAJPOOT et al, 2016). Therefore, for the first time in this study, the molecular evaluation of L. ayhanana in the genus was performed using the mtCOI sequence.…”
Section: Discussionmentioning
confidence: 99%
“…(MEYER & PAULAY, 2005;RACH et al, 2017). It is a common view for many researchers that a large number of molecular data is needed and that morphological, ecological and molecular synergy will reflect a correct taxonomic and higher level systematic study (KEMAL et al, 2019;RAJPOOT et al, 2016;TRANKNER et al, 2009;WAHLBERG et al, 2005).…”
Section: Discussionmentioning
confidence: 99%